The Factors That Related to Premenstrual Syndrome In Gunung Sari Village Pamijahan SubDistrict Bogor Regency - Rosalia Rahayu (LPPM ITEKES Mahardika, 2020)
In Indonesia, it was found that 95% of women of childbearing age have at least one symptom of Premenstrual Syndrome (PMS), with moderate to severe levels of 3.9%. This study aims to determine the frequency distribution of PMS incidents in Gunung Sari Village, Pamijahan District, Bogor Regency. This research is descriptive through a cross sectional approach with a population of all young women in Gunung Sari Village, Pamijahan District, Bogor Regency in 2017 as many as 195 people using total sampling technique. The variables measured were stress, consumption patterns, exercise patterns, age at menarche, BMI and PMS. Univariate and bivariate data analysis and research instruments using a questionnaire. The results of this study indicate that most of them experienced stress, 124 respondents (65.5%). Based on the consumption pattern, mostly good as much as 124 (65.5%). Based on the exercise pattern, most of it was routine as much as 124 (65.5%). The age of menarche was mostly normal as much as 105 (57.1%). For BMI,mostly normal (56.0%) and mostly experiencing PMS as many as 124 people (65.5%). The statistical test results were obtained for the p-value stress, consumption patterns, exercise patterns = 0.000. For menarche exam p-value = 0.635 and BMI p-value = 0.076. This shows a relationship between stress, consumption patterns and exercise patterns with the incidence of premenstrual syndrome in Gunung Sari Village, Pamijahan District, Bogor Regency. Meanwhile, the age of menarche and BMI had nothing relationship with the incidence of PMS. Provide additional material in the form of information needed by young women about STDs so that young women can avoid wrong perceptions when young women face PMS.